VALIDATION OF THE SPECTROFOTOMETRIC METHOD FOR THE DETERMINATION OF QUANTITATIVE COMPOSITION OF S-2,6-DIAGENOXIC ACID OF 3-METHYL-1,2,4-TRIAZOLYL- 5-THIOACETATE - Ivanovna, Kucherenko Lyudmila; SERGEEVICH, BIDNENKO OLEKSANDR; Vladimirovna, Khromylova Olga (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the work was to determine the validation characteristics for the designed procedure for quantitation of the (S)-2,6- diaminohexanoic acid substance, 3-methyl-1,2,4-triazolyl-5-thioacetate, by absorption spectrophotometry in the ultraviolet region. Methods: For study purposes, the substance (S)-2,6-diaminohexanoic acid of 3-methyl-1,2,4-triazolyl-5-thioacetate and a standard sample (SS) obtained from the State Enterprise Chemical Reagents Plantâ€ of the Scientific-Technological Complex Institute of Single Crystalsâ€ of the National Academy of Sciences of Ukraine, was used. In the course of our work, we used chemical, physical, physicochemical (absorption spectrophotometry in the ultraviolet region), and statistical methods of analysis. The study was carried out at the Laboratory for Standardization and Technology of Medicines at the Department of Pharmaceutical Chemistry at the Zaporizhia State Medical University (Ukraine). Results: In previous studies, we have developed a technique for spectrophotometric determination of the quantitative composition of (S)-2,6- diaminohexanoic acid of 3-methyl-1,2,4-triazolyl-5-thioacetate. The results of the conducted studies showed that the absorption curve in the UV region of the substance solution has a maximum absorption, namely: Î» = 238 nm. The results of the quantitation of the substance (S)-2,6-diaminohexanoic acid of 3-methyl-1,2,4-triazolyl-5-thioacetate prove that our technique is accurate and reproducible and meets the current requirements. In order for the developed methodology to ensure consistent and accurate analysis results, its validation was carried out. According to the requirements of the State Pharmacopoeia of Ukraine (DFU) (2 editions), the developed method for the quantitation of the substance was checked for such validation characteristics as specificity, linearity, range of use, accuracy, correctness, and robustness. Conclusion: As a result of the work, it was proved that the developed method of the quantitation of the substance (S)-2,6-diaminohexanoic acid of 3-methyl-1,2,4-triazolyl-5-thioacetate by spectrophotometric method is valid.